Pengaruh Model Pembelajaran Course Review Horay Berbantuan Media Kartu Masalah Terhadap Kemampuan Pemecahan Masalah - Inka Angreni Angreni; Abdul Rahman; Asdar Dollo (Tautologi: Journal of Mathematics Education, 2024)
This study aims to find out that the application of the Course Review Horay learning model has a positive effect on the problem solving abilities of class VII UPTD students of SMP Negeri 1 Parepare. This type of research is a type of experimental research. The variables studied in this study were the problem solving abilities of class VII UPTD SMP Negeri 1 Parepare as the dependent variable and the application of the course review horay learning model as the independent variable. The population of this study was students of class VII UPTD SMP Negeri 1 Parepare for the 2022/2023 academic year consisting of 10 (ten) classes. Sampling used Cluster Sampling or stratified random sampling, from 10 classes one class was taken randomly, namely class VII.5 as the experimental class. The instruments used in this study were problem solving ability tests (pretest & posttest) and validated student activity observation sheets. Based on descriptive statistical analysis, the average value of mathematics learning outcomes before applying the course review horay learning model was 35.63 and the average value of mathematics learning outcomes after applying the course review horay learning model was 72.19. Based on the inferential statistical analysis using the One Sample t-test, a significant value was obtained, p = 0.000 < 0.05, this means that H0 is rejected and H1 is accepted. So it can be concluded that the application of the course review horay learning model has a positive effect on the problem solving abilities of class VII UPTD SMPN 1 Parepare.